2018
DOI: 10.3389/fpsyg.2018.02235
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Hibernation in Antarctica

Abstract: Human activity in Antarctica has increased sharply in recent years. In particular during the winter months, people are exposed to long periods of isolation and confinement and an extreme physical environment that poses risks to health, well-being and performance. The present study aimed to gain a better understanding of processes contributing to psychological resilience in this context. Specifically, the study examined how the use of coping strategies changed over time, and the extent to which changes coincide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 45 publications
5
30
1
Order By: Relevance
“…Weber et al (2019) observed that negative affect was not altered by isolation, in contrast, positive affect tended to decrease as confinement progressed. A similar pattern of emotional response is identified in confinement under extreme environments (e.g., Sandal et al, 2018). Similarly, being confined with others can have paradoxical effects, such as expressing a need to interact with others but with little intimacy, or expecting others to establish close relationships but preferring to maintain little social interaction (Paul et al, 2010).…”
mentioning
confidence: 53%
“…Weber et al (2019) observed that negative affect was not altered by isolation, in contrast, positive affect tended to decrease as confinement progressed. A similar pattern of emotional response is identified in confinement under extreme environments (e.g., Sandal et al, 2018). Similarly, being confined with others can have paradoxical effects, such as expressing a need to interact with others but with little intimacy, or expecting others to establish close relationships but preferring to maintain little social interaction (Paul et al, 2010).…”
mentioning
confidence: 53%
“…Furthermore, mature defence mechanisms, using problem‐solving strategies, has been shown to be more beneficial than immature defence mechanisms (based on behavioural withdrawal of acting out) for coping purposes (Nicolas et al., 2016). Coping has also been shown to be influenced by the time of the year (seasonal effects), up to the extent that during winter months, winterers became more indifferent (Sandal, van de Vijver, & Smith, 2018). This sort of ‘psychological hibernation’ has been suggested to be a coping strategy in itself.…”
Section: Discussionmentioning
confidence: 99%
“…Nicolas and colleagues investigated the impact of a 1-year wintering in Concordia on affective, social, personality and cognitive outcomes (Nicolas, Suedfeld, Weiss, & Gaudino, 2016). More specifically, the the extent to which these changes were linked with changes in mood and sleep (Sandal et al 2018). They found that at midwinter, when conditions were harshest, resources were more depleted, participants were less involved in any form of coping, and reported less positive affect (effect sizes between 0.32 and 0.82 for coping strategies, depending on use of linear or quadratic time-based models; effect size of 0.43 for positive affect).…”
Section: Psychology and Neurosciencementioning
confidence: 99%
“…When responding, participants were asked to think about how they react when confronted with a problem and answer on a 4-point scale ranging from 1 (seldom or never) to 4 (very often). The UCL has demonstrated adequate validity and reliability in prior studies (Sandal, van der Vijver, & Smith, 2018;Sandal, Endresen, Vaernes, & Ursin, 1999).…”
Section: Measures Pre-expedition Questionnairementioning
confidence: 95%